SYSTEMATIC LITERATURE REVIEW: KOMITMEN DAN KEPUASAN KERJA TERHADAP KINERJA KADER PUSKESMAS: A SYSTEMATIC LITERATURE REVIEW: COMMITMENT AND JOB SATISFACTION TOWARDS THE PERFORMANCE OF PUBLIC HEALTH CENTRE CADRES - Hesty Yuliasari; Reni Merta Kusuma (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2021)
Introduction Public health promotion and monitoring carried out by community-assisted health center managers. The community is given the understanding that health efforts need to be made by all parties, both from the government and the community. Cadres are people who are formed to play an important role and have a strong commitment and dedication to move the organization to realize its vision and mission. Cadres are expected to have work commitment and satisfaction with their performance. Method This study aims to identify the commitment and job satisfaction of cadres to the performance of community health center cadres. The method used in this research is Systematic Literature Review (SLR) of journal papers published from 2010-2020. Results Articles that did not match the inclusion criteria were issued, leaving 63 articles relevant for quality results, so the researchers screened the articles again by applying the PICOC criteria. There were 13 articles which showed that they constituted 21 percent of 63 articles or it could be said that only 11 percent of the total 116 articles found in the online database search. Based on the results of literature analysis on selected journals as many as 13 journals, each variable has a coverage proportion of 53.8% for job satisfaction, 53.8% for commitment to organization and 46.15% for performance variables. In the variable job satisfaction the proportion of 53.8%, namely 7 journals from 13 selected journals that discuss job satisfaction. Conclusions and Recommendation The active role of cadres on job satisfaction shows the cadre's performance and the implementation of self-commitment and work commitment related to the health center. Commitment of cadres can be seen in their affective commitment to the organization where the increased performance of cadres is not only based on incentives, but the existence of self-development and increasing knowledge will increase cadre performance. Keywords: Commitment, Job satisfaction, Job performance, Public health center cadres ABSTRAKPendahuluan Promosi dan pemantauan kesehatan masyarakat dilakukan oleh pengelola puskesmas binaan masyarakat. Masyarakat diberi pemahaman bahwa upaya kesehatan perlu dilakukan oleh semua pihak, baik dari pemerintah maupun masyarakat. Kader adalah orangorang yang dibentuk untuk memegang peranan penting dan memiliki komitmen dan dedikasi yang kuat untuk menggerakkan organisasi guna mewujudkan visi dan misinya. Kader diharapkan memiliki komitmen kerja dan kepuasan terhadap kinerjanya. Metode Penelitian ini bertujuan untuk mengetahui komitmen dan kepuasan kerja kader terhadap kinerja kader puskesmas. Metode yang digunakan dalam penelitian ini adalah systematic literature review (SLR) artikel jurnal yang diterbitkan tahun 2010-2020 dengan kriteria PICOC. Hasil Menyisakan 13 artikel yang mana menunjukkan bahwa artikel-artikel tersebut merupakan 21 persen dari 63 artikel atau bisa dikatakan hanya 11 persen dari total 116 artikel yang ditemukan dalam pencarian database online. Berdasarkan hasil analisis literatur pada jurnal terpilih sebanyak 13 jurnal, masing-masing variabel memiliki persentase cakupan sebesar 53,8 % untuk Kepuasan kerja, 53,8% untuk komitmen terhadap organisasi, dan 46,15 % untuk variabel kinerja. Pada variabel kepuasan kerja persentase sebesar 53,8 % yaitu 7 jurnal dari 13 jurnal terpilih yang membahas mengenai kepuasan kerja. Kesimpulan dan Saran Adanya peran aktif kader dalam mencapai kepuasan kerjanya menunjukkan kinerja kader dan implementasi terhadap komitmen diri maupun komitmen kerja berkaitan dengan puskesmas. Komitmen kader terlihat dalam komitmen afektifnya terhadap organisasi dimana kinerja kader yang meningkat tidak hanya berdasarkan insentif, namun adanya pengembangan diri dan peningkatkan pengetahuan akan meningkatkan kinerja kader Kata kunci: Komitmen, Kepuasan kerja, Kinerja , Kader Puskesmas